High density lipoprotein: guardian of the vascular system? - Packard, C; Nunn, A; Hobbs, R (2002)
The role of low-density lipoprotein in the development of coronary heart disease (CHD) is well recognised. There is also growing evidence that high-density lipoprotein cholesterol (HDL-C) is a powerful inverse predictor for premature CHD and that maintaining a high HDL-C level may guard against atherosclerosis. Patients with low HDL-C levels often also have central obesity, insulin resistance and other features of the metabolic syndrome. This syndrome is both increasingly common and strongly implicated in the growing worldwide epidemic of type 2 diabetes. HDL-C may be increased by lifestyle changes, e.g. weight loss, physical activity and smoking cessation. Pharmacological agents such as fibrates, niacin and statins have also been shown significantly to elevate HDL-C. Although current guidelines are beginning to recognise the protective role of HDL-C level in preventing coronary events, HDL-C should be adopted soon as a target for intervention in its own right.